Visuospatial working memory is severely impaired in Bálint syndrome patients. (August 2015) - Funayama, Michitaka; Nakagawa, Yoshitaka; Sunagawa, Kosaku
Abstract: Although it has been proposed that visuospatial working memory may be impaired in Bálint syndrome patients, neither a systematic study concerning this proposal nor a comparison with patients having right-parietal damage has been made. Visuospatial working memory was assessed for six Bálint syndrome patients and members of two control groups—one composed of individuals with right-parietal damage ( n  = 15) and a second of age- and gender-matched healthy individuals ( n  = 26). We placed special emphasis on patients with a mild form of Bálint syndrome who can judge positional relationships between two objects. First, the participants were subjected to delayed visuospatial matching tasks. Next, their visuospatial-temporal integration abilities were assessed using a shape-from-moving-dots task. Visuospatial working memory was impaired for Bálint syndrome patients compared with controls according to the results of the tests. The differences between the Bálint syndrome and control subjects remained when only data for patients with the mild form of Bálint syndrome were included. We conclude that visuospatial working memory may be severely impaired in Bálint syndrome patients and, therefore, might influence their inability to properly execute movements and behaviours associated with daily living.